PERSEPSI ORANGTUA TENTANG PENDIDIKAN MORAL RELIGIUS DALAM KELUARGA DAN DAMPAKNYA BAGI KEHIDUPAN REMAJA DI DUSUN CANDEN, KEL. KUTOWINANGUN LOR, KEC. TINGKIR, SALATIGA - Nia Kurniawati; Mashlihatul Umami (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2023)
This study aims to describe the parents' perception of religious moral education in the family, to describe the application of religious moral education in the family, and to determine the impact of the application of religious moral education in the family for the lives of adolescents. The sampling technique used is purposive sampling. This study uses a descriptive qualitative approach. The research data was obtained through observation, interviews and documentation. The results of this study found that (1) Parents have a perception that religious moral education in the family is very important for the survival of adolescents in the future (2) In implementing religious moral education in the family, parents provide an example, get teenagers to carry out what is taught by Islam, carry out orders and stay away from Allah's prohibitions, advise and supervise and observe the development of adolescent religious attitudes. (3) the impact of the application of religious moral education for the lives of adolescents is to increase the obedience of adolescents in carrying out their obligations, showing gratitude for His blessings, having high fighting power, carrying out what Allah has commanded, and leaving Allah's prohibitions. Keywords: Parents' Perceptions, Religious Moral Education, Adolescents